A DAF membrane based on ultrasonic spraying method and a preparation method and application thereof
Patent Information
- Application Number
- CN202611339667.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明目的是针对现有喷涂法制备DAF膜时存在的胶液雾化不均、涂层厚度偏差大、溶剂残留超标、气泡与针孔缺陷多、填料团聚、基材易溶胀起皱等技术问题,提供一种基于超声喷涂法的DAF膜及其制备方法、应用,通过多维度工艺优化,实现DAF膜综合性能的显著提升,简化工艺流程、降低生产成本,适配先进封装需求,推动喷涂法在DAF膜制备中的产业化应用
1、本发明基于超声波喷涂法的DAF膜及其制备方法,可显著提高涂层均匀性与表面质量:通过超声雾化与静电吸附协同喷涂,结合多层交叉喷涂方式,制备的DAF膜厚度精度提升至±0.8μm,表面无针孔、气泡、流挂等缺陷,表面粗糙度Ra<0.3μm,适配大尺寸晶圆与超薄芯片的封装需求。
Smart Images

Figure CN123004086A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor technology, and more specifically, to a DAF film based on ultrasonic spraying, its preparation method, and its application. Background Technology
[0002] Disk-attachment film (DAF) is a critical bonding material in semiconductor packaging, used to achieve high-performance bonding between the chip and the substrate and lead frame. Its performance directly determines the mechanical strength, thermal conductivity, and long-term reliability of semiconductor devices. With the miniaturization, ultra-thinning, and high-density integration of semiconductor devices, and the popularization of advanced packaging technologies such as Fan-Out and 3D ICs, higher requirements are placed on the thickness uniformity, bonding strength, thermal conductivity, and surface quality of DAF films.
[0003] Currently, the mainstream fabrication process for DAF films is slot extrusion coating. However, this process has drawbacks such as high equipment investment, stringent requirements on adhesive viscosity, and difficulty in adapting to irregularly shaped substrates or localized spraying needs. Spray coating, as a flexible and efficient thin film fabrication process, has advantages such as simple equipment, convenient operation, strong adaptability, and the ability to achieve precise localized spraying. It has been tested in the fabrication of DAF films, and in the thin film deposition stage of semiconductor packaging, spray coating has become one of the mainstream choices alongside spin coating and printing.
[0004] However, existing spraying methods for preparing DAF films still have many technical defects, which seriously limit their industrial application: First, the atomization of the adhesive is uneven, and the droplet size difference in ordinary spraying is large, resulting in large coating thickness deviation, high surface roughness, and defects such as pinholes and sagging. Second, during the spraying process, the evaporation rate of the adhesive solvent is difficult to control, which easily generates bubbles, and the subsequent drying and curing is insufficient, resulting in excessive solvent residue (usually >1%). This easily leads to problems such as delamination and voids during subsequent encapsulation, especially when mounting large-size chips, where the bubble problem is more prominent. Third, functional fillers (such as thermally conductive fillers) are prone to agglomeration in the adhesive, resulting in uneven adhesive layer performance after spraying and poor stability of thermal conductivity and adhesion. Fourth, the substrate is prone to swelling and wrinkling during spraying, which leads to a decrease in coating smoothness and affects the accuracy of subsequent chip mounting. This is because the localized concentration of solvent impact during spraying easily causes stress concentration on the film surface.
[0005] In the prior art, some patents (such as US20220028819A1 and US2011319513A1) attempt to improve the spraying process to optimize the performance of DAF films, but most focus on adjusting a single parameter and fail to address the aforementioned defects from multiple dimensions such as atomization effect, filler dispersion, substrate fixation, and curing process. For example, optimizing only the spraying speed and distance fails to solve the problems of uneven adhesive atomization and filler agglomeration; while increasing the drying time to control solvent residue leads to reduced production efficiency and brittle adhesive layer.
[0006] Furthermore, existing spraying processes mostly employ ordinary air spraying, resulting in coarse atomized droplets and a lack of effective substrate fixation measures, further exacerbating problems such as poor coating uniformity and film wrinkling. Therefore, developing an ultrasonic spraying DAF film preparation process that can overcome the aforementioned technical deficiencies, achieve synergistic improvement in multiple performance aspects, and is simple and scalable has become an urgent need in the current semiconductor packaging materials field.
[0007] In view of this, the present invention is hereby proposed. Summary of the Invention
[0008] The purpose of this invention is to address the technical problems existing in the preparation of DAF films using existing spraying methods, such as uneven atomization of adhesive solution, large deviation in coating thickness, excessive solvent residue, numerous defects such as bubbles and pinholes, filler agglomeration, and easy swelling and wrinkling of the substrate. This invention provides a DAF film based on ultrasonic spraying, its preparation method, and its application. Through multi-dimensional process optimization, the overall performance of the DAF film is significantly improved, the process flow is simplified, production costs are reduced, it adapts to advanced packaging requirements, and promotes the industrial application of spraying methods in DAF film preparation.
[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A DAF membrane based on ultrasonic spraying method comprises the following components in parts by weight: 20-40 parts modified functional filler, 60-70 parts epoxy resin, 30-40 parts polyimide resin, 4-8 parts latent curing agent, and 1.5-2.5 parts first coupling agent. The modified functional filler includes a thermally conductive filler, a second coupling agent, and a dispersant, with a mass ratio of 100:3~5:0.3~0.8. The particle size D90 of the modified functional filler is <4μm.
[0010] Furthermore, the thermally conductive filler is at least one of hexagonal boron nitride, aluminum nitride, silicon carbide, and silicon nitride.
[0011] Further, the second coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.
[0012] Further, the dispersant is at least one of sodium polycarboxylate, ammonium polycarboxylate, sodium salt of polymethyl methacrylate-ethyl acrylate copolymer, and sodium salt of maleic acid-acrylic acid copolymer.
[0013] Further, the epoxy resin is at least one of bisphenol A type epoxy resin E-51, bisphenol A type epoxy resin E-44, bisphenol F type epoxy resin NPEF-170, and alicyclic epoxy resin ERL-4221.
[0014] Furthermore, the polyimide resin is at least one of pyromellitic polyimide resin, bisphenol A polyimide resin, and polyetherimide resin.
[0015] Furthermore, the latent curing agent is at least one of 2-ethyl-4-methylimidazolium, 1-benzyl-2-methylimidazolium, 2-phenyl-4,5-dihydroxyimidazolium, and methyltetrahydrophthalic anhydride.
[0016] Further, the first coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and vinyltriethoxysilane.
[0017] Furthermore, the epoxy resin and polyimide resin comprise a total of 100 parts.
[0018] Furthermore, the DAF membrane based on ultrasonic spraying also includes the following components in parts by weight: 0.1 to 0.2 parts of defoamer, 0.2 to 0.4 parts of leveling agent, and 0.3 to 0.6 parts of toughening agent.
[0019] The above-mentioned method for preparing DAF film based on ultrasonic spraying includes the following steps: Step 1: Prepare modified functional fillers; Step 2: Prepare the spray adhesive solution; Step 3: Fix and preheat the protective film; Step 4: Ultrasonic-electrostatic synergistic spraying; Step 5: Gradient temperature-controlled drying and high-temperature curing.
[0020] Furthermore, the method for preparing the modified functional filler in step 1 includes: Step 1.1: Mix the thermally conductive filler with the second coupling agent in proportion, so that the second coupling agent is evenly coated on the surface of the thermally conductive filler; Step 1.2: Add dispersant according to the ratio and mix using a combination of high-speed dispersion and ultrasonic vibration.
[0021] Furthermore, the method for preparing the spray adhesive in step 2 includes: Step 2.1: Mix epoxy resin and polyimide resin in proportion as the main resin, add the remaining components and solvent in proportion, mix thoroughly to ensure that all components are completely dissolved; Step 2.2: Vacuum degassing and filtration; Step 2.3: Let it stand and mature to obtain the spray adhesive.
[0022] Furthermore, the method for fixing and preheating the protective film in step 3 includes: laying the protective film flat on the vacuum adsorption heating plate, turning on the vacuum adsorption device, and preheating the heating plate at the same time.
[0023] Furthermore, the mixing process in step 1.1 involves stirring at a constant temperature of 70~90℃ for 1.5~2.5 hours.
[0024] Furthermore, in step 1.1, a protective gas is introduced during the mixing process, the protective gas including at least one of nitrogen, helium, neon, and argon.
[0025] Furthermore, in step 1.2, the high-speed dispersion speed is 2500~3500 rpm, and the dispersion time is 25~35 min.
[0026] Furthermore, in step 1.2, the oscillation frequency of the ultrasonic oscillation is 40~60kHz, and the oscillation time is 25~35min.
[0027] Further, the solvent used for mixing in step 2.1 is at least one of butanone, cyclohexanone, and propylene glycol methyl ether acetate.
[0028] Furthermore, the mixing process in step 2.1 involves stirring at room temperature for 30-60 minutes.
[0029] Furthermore, the vacuum degassing pressure in step 2.2 is -0.09 to -0.095 MPa.
[0030] Furthermore, the filter membrane used in step 2.2 has a pore size of 4~6μm.
[0031] Furthermore, the settling and ripening time in step 2.3 is 1.5~3 hours.
[0032] Furthermore, the solid content of the spray adhesive obtained in step 2.3 is 30~40wt%, and the viscosity is 500~1500mPa·s.
[0033] Furthermore, the pressure of vacuum adsorption in step 3 is 0.06~0.08MPa.
[0034] Furthermore, in step 3, the preheating temperature of the heating plate is 50~60℃.
[0035] Furthermore, step 4, the ultrasonic-electrostatic synergistic spraying method, includes: using ultrasonic spraying equipment and applying electrostatics by an external electric field, sending the spraying adhesive into an ultrasonic atomizer, and spraying the adhesive into tiny droplets.
[0036] Furthermore, step 4, the ultrasonic-electrostatic synergistic spraying process, adopts a multi-layer thin-spray-cross spraying method.
[0037] Furthermore, in step 4, the ultrasonic atomization frequency is 80~120kHz.
[0038] Furthermore, the diameter D of the microdroplets mentioned in step 4 is 5~10 μm.
[0039] Furthermore, the voltage applied in step 4 is 8~25kV.
[0040] Furthermore, in step 4, the spraying air pressure is 0.1 MPa to 0.2 MPa, the spraying distance is 15 to 25 cm, and the spraying speed is 5 to 12 m / min.
[0041] Furthermore, in step 4, during the ultrasonic-electrostatic synergistic spraying process, the spray gun is always perpendicular to the protective film surface.
[0042] Furthermore, in step 4, the thickness of a single layer of wet film in the multi-layer thin spray is 8~15μm, and the total thickness of the wet film is 40~180μm.
[0043] Furthermore, in step 4, the cross-spraying angle between adjacent layers is 45°~90°.
[0044] Furthermore, in step 4, the overlap rate of the trajectories of two adjacent spray coats during the single-layer spraying process is 30% to 50%.
[0045] Furthermore, the gradient temperature-controlled drying and high-temperature curing method in step 5 includes: sending the sprayed wet film together with the vacuum adsorption heating plate into a multi-zone gradient oven, and sequentially staying in each temperature zone with an increasing temperature gradient to obtain a DAF film.
[0046] Furthermore, the multi-zone gradient oven includes four temperature zones, with temperature gradients of 65~75℃, 90~100℃, 110~120℃, and 125~135℃ respectively.
[0047] Furthermore, the dwell time in each temperature zone is 1-2 minutes, and the total dwell time in the four temperature zones is 5-8 minutes.
[0048] The above-mentioned DAF film based on ultrasonic spraying method and the DAF film prepared by the above preparation method are used in 8-12 inch wafer and chip packaging.
[0049] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention relates to a DAF film based on ultrasonic spraying and its preparation method, which can significantly improve coating uniformity and surface quality: through ultrasonic atomization and electrostatic adsorption synergistic spraying, combined with multi-layer cross-spraying, the thickness accuracy of the prepared DAF film is improved to ±0.8μm, the surface is free of defects such as pinholes, bubbles, and sagging, and the surface roughness Ra<0.3μm, which is suitable for the packaging requirements of large-size wafers and ultra-thin chips.
[0050] 2. This invention relates to a DAF film based on ultrasonic spraying and its preparation method, which can achieve comprehensive performance optimization: through the optimization of modified functional filler dispersion, the thermally conductive filler is uniformly dispersed, and the thermal conductivity of the prepared DAF film is increased to ≥1.1W / (m·K), the bonding strength is >9MPa, and it also has excellent flexibility and high temperature resistance; the gradient temperature-controlled curing process ensures that the solvent residue is <0.8% and the gel rate is stable at 22-38%, avoiding problems such as delamination and voids during subsequent encapsulation, improving the reliability of encapsulation, and solving the technical defects of existing DAF films such as many bubbles and uneven thermal conductivity during application.
[0051] 3. The present invention provides a DAF film preparation method based on ultrasonic spraying, which is flexible and scalable: the investment cost of ultrasonic spraying equipment is lower than that of slot extrusion coating equipment, it is easy to operate, can achieve local precision spraying, and is suitable for irregularly shaped substrates and wafers of different sizes; at the same time, the preparation process of the present invention does not require complex equipment modification, can be directly adapted to existing production lines, has high production efficiency, reduces production costs, and facilitates large-scale industrial production.
[0052] 4. The present invention provides a DAF film preparation method based on ultrasonic spraying, which has good stability and strong adaptability of the sprayed substrate protective film: by fixing the protective film through vacuum adsorption, the problem of substrate swelling and wrinkling during spraying is effectively solved, ensuring the smoothness of the coating, while improving the adhesion between the adhesive layer and the substrate, reducing the risk of delamination, and can be adapted to wafers of different sizes from 8 to 12 inches, thus broadening the application range of sprayed DAF film. Attached Figure Description
[0053] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0054] Figure 1 This is a schematic diagram of the spray gun's travel trajectory and cross-spraying angle during the cross-spraying process of adjacent two layers in this invention; Figure 2 This is a schematic diagram of the spray gun's travel trajectory and trajectory overlap rate during the single-layer spraying process of this invention. Detailed Implementation
[0055] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0056] A DAF membrane based on ultrasonic spraying method comprises the following components in parts by weight: 20-40 parts modified functional filler, 60-70 parts epoxy resin, 30-40 parts polyimide resin, 4-8 parts latent curing agent, and 1.5-2.5 parts first coupling agent.
[0057] In some embodiments, the modified functional filler includes a thermally conductive filler, a second coupling agent, and a dispersant, with a mass ratio of 100:3~5:0.3~0.8, including but not limited to 100:3:0.3, 100:3:0.5, 100:3:0.8, 100:4:0.3, 100:4:0.5, 100:4:0.8, 100:5:0.3, 100:5:0.5, and 100:5:0.8.
[0058] In some embodiments, the particle size D90 of the modified functional filler is < 4 μm.
[0059] Furthermore, the thermally conductive filler is at least one of hexagonal boron nitride (h-BN), aluminum nitride (AlN), silicon carbide, and silicon nitride (Si3N4).
[0060] Further, the second coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane (KH-560), γ-aminopropyltriethoxysilane (KH-550), vinyltriethoxysilane (KH-151), and γ-methacryloyloxypropyltrimethoxysilane (KH-570).
[0061] Further, the dispersant is at least one of sodium polycarboxylate, ammonium polycarboxylate, sodium salt of polymethyl methacrylate-ethyl acrylate copolymer, and sodium salt of maleic acid-acrylic acid copolymer.
[0062] In some embodiments, the epoxy resin and polyimide resin comprise a total of 100 parts.
[0063] In some embodiments, the epoxy resin is at least one of bisphenol A type epoxy resin E-51, bisphenol A type epoxy resin E-44, bisphenol F type epoxy resin NPEF-170, and alicyclic epoxy resin ERL-4221.
[0064] In some embodiments, the polyimide resin is at least one of homopolymer polyimide resin (PI-2611), bisphenol A polyimide resin (PI-3000), and polyetherimide resin (PEI-1000).
[0065] In some embodiments, the latent curing agent is at least one of 2-ethyl-4-methylimidazolium (2E4MZ), 1-benzyl-2-methylimidazolium (1B2MZ), 2-phenyl-4,5-dihydroxyimidazolium (PHI), and methyltetrahydrophthalic anhydride.
[0066] In some embodiments, the first coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane (KH-560), γ-aminopropyltriethoxysilane (KH-550), γ-methacryloyloxypropyltrimethoxysilane (KH-570), and vinyltriethoxysilane (KH-151).
[0067] In some embodiments, the DAF film based on ultrasonic spraying further includes the following components in parts by weight: 0.1 to 0.2 parts of defoamer, 0.2 to 0.4 parts of leveling agent, and 0.3 to 0.6 parts of toughening agent.
[0068] In some embodiments, the defoamer is at least one of polydimethylsiloxane (PDMS), polyether-modified polysiloxane (BYK-066N), and silicone-free polymer defoamer (BYK-054).
[0069] In some embodiments, the leveling agent is at least one of the following: organosilicon leveling agent BYK-333, polyether-modified siloxane leveling agent BYK-3500, acrylate leveling agent BYK-352, and BYK358.
[0070] In some embodiments, the toughening agent is at least one of carboxyl-terminated butadiene-acrylonitrile rubber (CTBN), hydroxyl-terminated butadiene-acrylonitrile rubber (HTBN), polyethersulfone (PES), polyurethane-modified epoxy toughening agent, and core-shell structured acrylate toughening agent.
[0071] The above-mentioned method for preparing DAF films based on ultrasonic spraying, with ultrasonic spraying as the core and each step working together to achieve multi-performance optimization, specifically includes the following steps: Step 1: Prepare modified functional fillers; Step 2: Prepare the spray adhesive solution; Step 3: Fix and preheat the protective film; Step 4: Ultrasonic-electrostatic synergistic spraying; Step 5: Gradient temperature-controlled drying and high-temperature curing; Step 6: Post-processing.
[0072] In some embodiments, the method for preparing the modified functional filler in step 1 includes: Step 1.1: Mix the thermally conductive filler and the second coupling agent in proportion, place them in a stirring tank and keep the temperature at 70~90℃ (including but not limited to 70℃, 75℃, 80℃, 85℃, 90℃) for 1.5~2.5h (including but not limited to 1.5h, 2h, 2.5h) to make the second coupling agent uniformly coat the surface of the thermally conductive filler, improve its compatibility with the main resin, and reduce agglomeration. Step 1.2: Then, add the dispersant in proportion and mix it using a combination of high-speed dispersion and ultrasonic vibration to prevent obvious agglomeration. Finally, a uniformly dispersed modified functional filler is obtained, which lays the foundation for ensuring the uniformity of the sprayed adhesive in the subsequent process.
[0073] In some embodiments, a protective gas is introduced into the stirred tank in step 1.1, and the protective gas includes at least one of nitrogen, helium, neon, and argon.
[0074] In some embodiments, the high-speed dispersion speed in step 1.2 is 2500~3500 rpm (including but not limited to 2500 rpm, 2600 rpm, 2800 rpm, 3000 rpm, 3200 rpm, 3500 rpm), and the dispersion time is 25~35 min (including but not limited to 25 min, 26 min, 28 min, 30 min, 32 min, 35 min), which initially breaks up the packing agglomerates.
[0075] In some embodiments, the oscillation frequency of the ultrasonic oscillation in step 1.2 is 40~60kHz (including but not limited to 40kHz, 45kHz, 50kHz, 55kHz, 60kHz), and the oscillation time is 25~35min (including but not limited to 25min, 26min, 28min, 30min, 32min, 35min), further refining the filler particle size to ensure that the modified functional filler particle size D90 < 4μm.
[0076] In some embodiments, the method for preparing the spray adhesive in step 2 includes: Step 2.1: Mix epoxy resin and polyimide resin in proportion as the main resin, and add modified functional filler, latent curing agent, first coupling agent, defoamer, leveling agent, toughening agent and solvent in proportion, mix thoroughly to make all components completely dissolved; Step 2.2: Vacuum degassing removes air bubbles from the adhesive solution, followed by filtration to remove impurities; Step 2.3: Allow to stand and mature to obtain a uniform, bubble-free, and impurity-free spray adhesive, ensuring that the spray adhesive can achieve fine atomization and uniform spraying, while avoiding spray gun clogging.
[0077] In some embodiments, the solvent used for mixing in step 2.1 is at least one of butanone, cyclohexanone, and propylene glycol methyl ether acetate.
[0078] In some embodiments, the mixing process in step 2.1 is to stir at room temperature for 30 to 60 minutes (including but not limited to 30 minutes, 40 minutes, 50 minutes, and 60 minutes).
[0079] In some implementations, the vacuum degassing pressure in step 2.2 is -0.09 to -0.095 MPa (including but not limited to -0.09 MPa, -0.091 MPa, -0.092 MPa, -0.093 MPa, -0.094 MPa, and -0.095 MPa).
[0080] In some implementations, the pore size of the filter membrane used in step 2.2 is 4~6μm (including but not limited to 4μm, 5μm, 6μm).
[0081] In some implementations, the settling and ripening time in step 2.3 is 1.5 to 3 hours (including but not limited to 1.5 hours, 2 hours, 2.5 hours, and 3 hours).
[0082] In some embodiments, the solid content of the spray adhesive obtained in step 2.3 is 30~40wt% (including but not limited to 30wt%, 32wt%, 35wt%, 36wt%, 38wt%, 40wt%), and the viscosity is 500~1500mPa·s (including but not limited to 500mPa·s, 600mPa·s, 800mPa·s, 1000mPa·s, 1200mPa·s, 1500mPa·s).
[0083] In some embodiments, the method of fixing and preheating the protective film in step 3 includes: laying the protective film flat on a vacuum adsorption heating plate, turning on the vacuum adsorption device, and firmly fixing the protective film on the heating plate to ensure that the protective film surface is flat and wrinkle-free; at the same time, the heating plate is preheated so that when the subsequently atomized sprayed adhesive comes into contact with the hot protective film surface, the solvent can evaporate quickly, reducing the solvent wetting time and avoiding swelling and wrinkling of the protective film surface caused by solvent impact, further improving the smoothness of the coating. This measure effectively solves the core defect of unstable sprayed substrate in the existing spraying process.
[0084] In some embodiments, the protective film in step 3 is selected from one of PET protective film, PI polyimide film, and PEN polyethylene naphthalate film.
[0085] In some embodiments, the pressure of vacuum adsorption in step 3 is 0.06~0.08MPa (including but not limited to 0.06MPa, 0.07MPa, and 0.08MPa).
[0086] In some implementations, the preheating temperature of the heating plate in step 3 is 50~60℃ (including but not limited to 50℃, 52℃, 55℃, 56℃, 58℃, and 60℃).
[0087] In some embodiments, step 4, the ultrasonic-electrostatic synergistic spraying method, includes: using ultrasonic spraying equipment and applying electrostatics with an external electric field, sending the prepared spraying adhesive into an ultrasonic atomizer, and using high-frequency ultrasonic vibration to break the spraying adhesive into uniformly sized micro-droplets for spraying. Compared with ordinary air spraying, the droplets of ultrasonic atomization are finer and more uniform, and the ultrasonic vibration can continuously disperse the particles in the slurry, reduce filler agglomeration, and at the same time reduce liquid impact force, minimizing film deformation.
[0088] In some implementations, the ultrasonic atomization frequency in step 4 is 80~120kHz (including but not limited to 80kHz, 90kHz, 100kHz, 110kHz, 120kHz).
[0089] In some embodiments, the diameter D of the microdroplet in step 4 is 5~10μm (including but not limited to 5μm, 6μm, 7μm, 8μm, 9μm, 10μm).
[0090] In some implementations, the voltage at which static electricity is applied in step 4 is 8~25kV (including but not limited to 8kV, 10kV, 12kV, 15kV, 16kV, 18kV, 20kV, 22kV, 25kV).
[0091] In some embodiments, the spraying air pressure in step 4 is 0.1 MPa to 0.2 MPa (including but not limited to 0.1 MPa, 0.12 MPa, 0.15 MPa, 0.16 MPa, 0.18 MPa, and 0.2 MPa), the spraying distance is 15 to 25 cm (including but not limited to 15 cm, 16 cm, 18 cm, 20 cm, 22 cm, and 25 cm), and the spraying speed is 5 to 12 m / min (including but not limited to 5 m / min, 6 m / min, 8 m / min, 9 m / min, 10 m / min, and 12 m / min).
[0092] Preferably, the spraying process adopts a "multi-layer thin spraying-cross spraying" method to further eliminate coating thickness deviation and ensure uniform coating thickness across the entire area.
[0093] Furthermore, during the spraying process, the spray gun is always perpendicular to the protective film surface, without any tilt angle.
[0094] Furthermore, the thickness of a single layer of wet film in multi-layer thin spraying is 8~15μm (including but not limited to 8μm, 10μm, 12μm, 15μm), and the total thickness of the wet film is 40~180μm (40μm, 50μm, 60μm, 80μm, 100μm, 120μm, 150μm, 180μm).
[0095] Furthermore, the cross-spraying angle is the angle between the travel trajectories of the spray guns in two adjacent spray layers, such as... Figure 1 As shown, the cross-spraying angle is 45°~90° (including but not limited to 45°, 50°, 60°, 70°, 80°, 90°), which eliminates problems such as stripes, uneven thickness, and local missing glue that occur when spraying according to a unidirectional walking trajectory.
[0096] Furthermore, during single-layer spraying, the spray gun travels in a parallel trajectory, such as... Figure 2 As shown, the trajectory overlap rate of two adjacent sprays during single-layer spraying (referring to the ratio of the lateral overlap width W of the subsequent spray gun trajectory to the effective width L of the single-layer spraying, W / L*100%) is 30%~50% (including but not limited to 30%, 35%, 40%, 45%, 50%). The trajectory overlap rate of 30%~50% can effectively compensate for the inherent defects of weak atomization and thin coating at the edge of single-layer spraying, avoid the problem of strip-shaped thin marks caused by excessive overlap and local glue buildup and pinholes caused by excessive overlap. Combined with the 45°-90° cross spraying method, the spraying blind spots are eliminated in all directions, further ensuring the uniformity of the coating thickness of the entire area.
[0097] In some embodiments, the gradient temperature-controlled drying and high-temperature curing method in step 5 includes: sending the sprayed wet film together with the vacuum adsorption heating plate into a multi-zone gradient oven, and sequentially stopping in each temperature zone with increasing temperature gradient, using a process of "low temperature pre-solvent removal - medium temperature deep solvent removal - high temperature curing" to obtain a DAF film.
[0098] Furthermore, the multi-zone gradient oven includes four temperature zones, with temperature gradients of 65-75℃ (including but not limited to 65℃, 68℃, 70℃, 72℃, 75℃), 90-100℃ (including but not limited to 90℃, 92℃, 95℃, 96℃, 98℃, 100℃), 110-120℃ (including but not limited to 110℃, 112℃, 115℃, 116℃, 118℃, 120℃), and 125-135℃ (including but not limited to 125℃, 128℃, 130℃, 132℃, 135℃). Correspondingly, the 65-75℃ zone achieves low-temperature pre-solvent removal, the 90-100℃ and 110-120℃ zones achieve medium-temperature deep solvent removal, and the 125-135℃ zone achieves high-temperature curing.
[0099] Furthermore, the dwell time in each temperature zone is 1-2 minutes (including but not limited to 1 minute, 1.5 minutes, and 2 minutes), and the total dwell time in the four temperature zones is 5-8 minutes (including but not limited to 5 minutes, 6 minutes, 7 minutes, and 8 minutes).
[0100] In some implementations, the post-processing step 6 includes hot-pressing to laminate the release film, winding, die-cutting, and lamination.
[0101] Furthermore, the hot-pressing composite temperature is 65~75℃ (including but not limited to 65℃, 68℃, 70℃, 72℃, 75℃), and the pressure is 0.15~0.25MPa (including but not limited to 0.15MPa, 0.16MPa, 0.18MPa, 0.20MPa, 0.22MPa, 0.25MPa).
[0102] Furthermore, the winding is performed with a constant tension of 6~14N (including but not limited to 6N, 8N, 10N, 12N, 14N).
[0103] Furthermore, the die-cutting method includes: cooling the DAF film to room temperature, peeling off the protective film, die-cutting it into standard sizes (such as 8 inches or 12 inches), and removing excess waste from the edges after die-cutting.
[0104] Furthermore, the lamination method includes: applying a layer of acrylic tape onto the die-cut DAF film to obtain the finished product.
[0105] The above-mentioned DAF film based on ultrasonic spraying method and the DAF film prepared by the above preparation method are used in 8-12 inch wafer and chip packaging.
[0106] Example 1 A DAF membrane preparation process based on ultrasonic spraying method, the specific steps of which are as follows: Step 1: Hexagonal boron nitride (h-BN) and γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) were mixed at a mass ratio of 100:3 and stirred at 70℃ for 2.5 h under nitrogen protection to complete surface modification. Then, 0.3% of sodium polycarboxylate (by mass of total hexagonal boron nitride) was added and dispersed at 2500 rpm for 35 min, followed by ultrasonic vibration at 40 kHz for 30 min to obtain the modified functional filler (D90=3.8μm). Step 2: Using bisphenol A type epoxy resin (E-51) and pyromellitic polyimide resin (PI-2611) at a mass ratio of 6:4 as the main resin, add 25% of modified functional filler, 4% of latent curing agent (2-ethyl-4-methylimidazolium (2E4MZ)), 1.5% of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) coupling agent, and 0.1% of defoamer (polydimethyl... 0.2% of PDMS, 0.2% of leveling agent (BYK-333), and 0.3% of toughening agent (carboxyl-terminated butadiene-acrylonitrile rubber (CTBN)) were added to a solvent (butanone) of 20% of the total mass of the main resin. The mixture was stirred at room temperature for 30 min to dissolve, degassed under vacuum at -0.09 MPa for 55 min, filtered through a 4 μm pore size filter membrane, and allowed to stand for 3 h to mature, resulting in a spray adhesive with a solid content of 30 wt% and a viscosity of 500 mPa·s. Step 3: Lay the PET protective film flat on the vacuum adsorption heating plate, turn on the vacuum adsorption device, and set the adsorption pressure to 0.07MPa to firmly fix the PET protective film on the heating plate; at the same time, preheat the heating plate to 50℃. When the atomized sprayed adhesive comes into contact with the hot film surface, the solvent can evaporate quickly. Step 4, Ultrasonic-Electrostatic Co-coating: Ultrasonic spraying equipment is used with an atomization frequency of 80kHz, an electrostatic voltage of 10kV, a spraying distance of 15cm, a spraying speed of 5m / min, a single-pass wet film thickness of 8μm, a cross-spraying angle of 45°, an overlap rate of 30%, and a cumulative wet film thickness of 40μm. The spraying air pressure is kept stable at 0.15MPa and finely adjusted in 0.05MPa increments as needed. Step 5: Place the product into a 4-zone gradient oven with temperature gradients of 70℃, 95℃, 115℃, and 130℃. Hold the product in each zone for 2 minutes, for a total holding time of 8 minutes. Monitor and adjust parameters online to control the volatile matter content to 0.7% and the gelation rate to 22%. Step 6: Hot-press the second PET protective film at 65℃ and 0.15MPa, wind it up with constant tension of 6N, precisely cut it to a width of 300mm, and die-cut it into 8-inch round sheets. After passing the inspection, vacuum pack it and store it at 5℃ away from light to obtain a finished DAF film with a thickness of 10μm.
[0107] Example 2 A method for preparing a DAF film based on ultrasonic spraying, the specific steps of which are as follows: Step 1: Hexagonal boron nitride (h-BN) and γ-aminopropyltriethoxysilane (KH-550) were mixed at a mass ratio of 100:4 and stirred at 80℃ for 2 hours under nitrogen protection to complete surface modification. Then, 0.5% of the total mass of hexagonal boron nitride in ammonium polycarboxylate was added, and the mixture was dispersed at 3000 rpm for 30 minutes, followed by ultrasonic vibration at 50 kHz for 30 minutes to obtain the modified functional filler (D90=3.5μm). Step 2: Using bisphenol F type epoxy resin (F-51) and bisphenol A type polyimide resin (PI-3000) at a mass ratio of 6.5:3.5 as the main resin, add 25% of modified functional filler, 4% of latent curing agent (2-ethyl-4-methylimidazolium (2E4MZ)), 1.5% of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) coupling agent, and 0.1% of defoamer (polydimethyl... 0.2% of PDMS, 0.2% of leveling agent (BYK-333), and 0.3% of toughening agent (carboxyl-terminated butadiene-acrylonitrile rubber (CTBN)) were added to a solvent (butanone) of 20% of the total mass of the main resin. The mixture was stirred at room temperature for 45 min to dissolve, degassed under vacuum at -0.092 MPa for 45 min, filtered through a 5 μm pore size filter membrane, and allowed to stand for 2.2 h to mature, resulting in a spray adhesive with a solid content of 35 wt% and a viscosity of 1000 mPa·s. Step 3: Lay the PET protective film flat on the vacuum adsorption heating plate, turn on the vacuum adsorption device, and set the adsorption pressure to 0.07MPa to firmly fix the PET protective film on the heating plate; at the same time, preheat the heating plate to 50℃. When the atomized sprayed adhesive comes into contact with the hot film surface, the solvent can evaporate quickly. Step 4: Use ultrasonic spraying equipment with an atomization frequency of 100kHz, electrostatic voltage of 15kV, spraying distance of 20cm, spraying speed of 8m / min, single-pass wet film thickness of 12μm, cross-spraying angle of 60°, overlap rate of 40%, and cumulative spraying to a total wet film thickness of 120μm; maintain the spraying air pressure at 0.15MPa, and finely adjust in 0.05MPa increments as needed; Step 5: Place the product into a 4-zone gradient oven with temperature gradients of 70℃, 95℃, 115℃, and 130℃. Hold the product in each zone for 1.5 minutes, for a total holding time of 6 minutes. Monitor and adjust parameters online to control the volatile matter content to 0.6% and the gelation rate to 30%. Step 6: Hot-press the second PET protective film at 70℃ and 0.2MPa, roll it up with 10N constant tension, precisely cut it to 300mm width, and die-cut it into 8-inch round sheets. After passing the inspection, vacuum pack it and store it at 10℃ away from light to obtain a DAF film with a thickness of 22μm.
[0108] Example 3 A method for preparing a DAF film based on ultrasonic spraying, the specific steps of which are as follows: Step 1: Hexagonal boron nitride (h-BN) and γ-methacryloyloxypropyltrimethoxysilane (KH-570) were mixed at a mass ratio of 100:5 and stirred at 90℃ for 1.5 h under nitrogen protection to complete surface modification; then 0.8% of the total mass of hexagonal boron nitride in ammonium polycarboxylate was added, and the mixture was dispersed at 3500 rpm for 25 min, followed by ultrasonic vibration at 60 kHz for 30 min to obtain the modified functional filler (D90=3.2μm). Step 2: Using bisphenol F type epoxy resin (NPEF-170) and polyetherimide resin (PEI-1000) mixed at a mass ratio of 7:3 as the main resin, add 35% of modified thermally conductive filler, 8% of latent curing agent (2-ethyl-4-methylimidazolium (2E4MZ)), 2.5% of γ-methacryloyloxypropyltrimethoxysilane (KH-570) coupling agent, and 0.2% of defoamer (polydimethylsiloxane). Methylsiloxane (PDMS), 0.4% leveling agent (BYK-333), and 0.6% toughening agent (carboxyl-terminated butadiene-acrylonitrile rubber (CTBN)) were added to a solvent of 15% of the total mass of the main resin. The mixture was stirred at room temperature for 60 min to dissolve, degassed under vacuum at -0.095 MPa for 35 min, filtered through a 6 μm pore size filter membrane, and allowed to stand for 1.5 h to mature, resulting in a spray adhesive with a solid content of 40 wt% and a viscosity of 1500 mPa·s. Step 3: Lay the PET protective film flat on the vacuum adsorption heating plate, turn on the vacuum adsorption device, and set the adsorption pressure to 0.07MPa to firmly fix the PET protective film on the heating plate; at the same time, preheat the heating plate to 50℃. When the atomized sprayed adhesive comes into contact with the hot film surface, the solvent can evaporate quickly. Step 4: Use ultrasonic spraying equipment with an atomization frequency of 120kHz, electrostatic voltage of 20kV, spraying distance of 25cm, spraying speed of 12m / min, single-pass wet film thickness of 15μm, cross-spraying angle of 90°, overlap rate of 50%, and cumulative spraying to a total wet film thickness of 180μm; maintain the spraying air pressure at 0.15MPa, and finely adjust in 0.05MPa increments as needed; Step 5: Place the product into a 4-zone gradient oven with temperature gradients of 70℃, 95℃, 115℃, and 130℃. Hold the product in each zone for 1 minute, for a total holding time of 4 minutes. Monitor and adjust parameters online to control the volatile matter content to 0.5% and the gelation rate to 38%. Step 6: Hot-press the second PET protective film at 75℃ and 0.25MPa, wind it up with constant tension of 14N, precisely cut it to a width of 300mm, and die-cut it into 8-inch round sheets. After passing the inspection, vacuum pack it and store it at 15℃ away from light to obtain a finished DAF film with a thickness of 30μm.
[0109] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: In step 1, hexagonal boron nitride (h-BN) and γ-methacryloyloxypropyltrimethoxysilane (KH-570) are mixed at a mass ratio of 100:5 and stirred at a constant temperature of 90°C for 1.5 hours under nitrogen protection to complete surface modification. Subsequently, 0.8% of sodium polycarboxylate by mass of hexagonal boron nitride is added and mixed evenly. The remaining preparation steps are the same as in Example 1.
[0110] Comparative Example 2 The difference between this comparative example and Example 2 is as follows: Step 3: The PET protective film is laid flat on the vacuum adsorption heating plate. The vacuum adsorption device is not turned on, and the temperature of the heating plate is directly preheated to 50°C. When the atomized adhesive comes into contact with the hot film surface, the solvent can evaporate rapidly. The remaining preparation steps are the same as in Example 2.
[0111] Comparative Example 3 The difference between this comparative example and Example 3 is as follows: Step 4: Ordinary spraying equipment was used, with a spraying distance of 25cm, a spraying speed of 12m / min, a single-pass wet film thickness of 15μm, a cross-spraying angle of 90°, an overlap rate of 50%, and a cumulative wet film thickness of 180μm. The remaining preparation steps are the same as in Example 3.
[0112] Test case The DAF membranes prepared in Examples 1-3 and the DAF membranes prepared in Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in Table 1.
[0113] The thickness accuracy test method is based on GB / T 6672-2001 "Mechanical Measurement Method for Determination of Thickness of Plastic Films and Sheets".
[0114] The test method for adhesive strength is in accordance with GB / T 7754-1987 "Pressure-sensitive adhesive tape shear strength test method (adhesive side and back side)".
[0115] The test method for thermal conductivity is in accordance with GB / T 22588-2008 "Measuring thermal diffusivity or thermal conductivity by flash method".
[0116] The test method for solvent residue is based on GB / T 2793-2026 "Determination of nonvolatile matter content in adhesives".
[0117] The test method for gelation rate is based on GB / T 14074-2017 "Test Methods for Adhesives and Resins for Wood Industry".
[0118] The surface roughness test method is based on GB / T 31227-2014 "Method for measuring the surface roughness of sputtered thin films using atomic force microscopy".
[0119] The test methods for pinhole / bubble defect rate and film surface wrinkling rate are based on GB / T 47631-2026 "Scanning Microscopy Test Method for Apparent Quality of Optical Functional Thin Films".
[0120] Table 1 Performance test data of DAF membranes prepared in Examples 1-3 and Comparative Examples 1-3
[0121] Compared with Example 1, the modified functional filler in Comparative Example 1 was not dispersed into uniform microparticles by ultrasonic vibration, and micron-sized filler agglomerates were easily formed in the sprayed adhesive. In the ultrasonic electrostatic spraying process, nozzle clogging and large differences in atomized droplet size would occur, resulting in streaks, spots, and local thickness deviations in the sprayed DAF film, and defects such as pinholes and bubbles would easily appear. At the same time, filler agglomeration would destroy the continuous thermal conductive network, resulting in uneven distribution of thermal conductivity of the DAF film, and would also destroy the continuous resin phase, leading to a significant decrease in adhesive strength.
[0122] Compared to Example 2, in Comparative Example 2, the PET protective film was not vacuum-adsorbed during spraying; it relied solely on tension. This resulted in wavy wrinkles and localized gaps in the sprayed area. The mixed solvent further caused swelling and bulging of the film surface, disrupting the stable electric field of the ultrasonic electrostatic spraying. Uneven adsorption of atomized droplets led to appearance defects such as streaks, cloudiness, and missing adhesive at the edges, with thickness accuracy significantly exceeding standards. Simultaneously, an air insulation layer existed between the wrinkled and gapped areas and the preheating platen, reducing heat transfer efficiency. After gradient curing, solvent residue exceeded standards, gel rate fluctuated excessively, and the adhesive layer was prone to micro-cracks. The cured DAF film surface was uneven, making the hot-pressed release film prone to indentations and delamination. The roll material warped after winding. During downstream chip mounting, this resulted in large-area voids, tilting and cracking of ultra-thin chips, severe contamination during wafer dicing, and significantly reduced packaging yield and long-term device reliability.
[0123] Compared to Example 3, Comparative Example 3, step 4 of the spraying process only uses conventional air spraying equipment and does not employ ultrasonic atomization-electrostatic spraying. The adhesive droplets formed by high-pressure airflow tearing are large and unevenly distributed, easily leading to sagging, adhesive spots, and missing adhesive at the edges, significantly degrading the DAF film thickness accuracy. Simultaneously, the high-pressure airflow easily causes secondary agglomeration of the thermally conductive filler, and the large droplets carry air into the wet film, significantly increasing the number of pinholes and protrusions on the film surface after curing. Ordinary spraying results in excessive film thickness in a single pass, making it difficult to fully remove internal solvents, leading to excessive volatile content in the finished product, large fluctuations in gelation rate, and an uneven, rough film surface. This makes the hot-pressed release film prone to indentation and delamination. During chip packaging, the uneven surface and uneven filler distribution of the DAF film cause a significant increase in mounting voids, making ultra-thin chips prone to tilting, edge breakage, and chip contamination from filler debris during the dicing process, severely reducing packaging yield and long-term reliability of semiconductor devices.
[0124] Therefore, as can be seen from the comparative experiments, the DAF film prepared by the present invention is significantly superior to the DAF film prepared by the existing ordinary spraying method in terms of thickness accuracy, bonding strength, thermal conductivity, solvent residue, gel rate stability, surface quality and film surface flatness, effectively solving the core technical defects of the existing spraying method for preparing DAF film.
[0125] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A DAF film based on ultrasonic spraying, characterized in that, It comprises the following components by weight: 20-40 parts modified functional filler, 60-70 parts epoxy resin, 30-40 parts polyimide resin, 4-8 parts latent curing agent, and 1.5-2.5 parts first coupling agent; The modified functional filler includes a thermally conductive filler, a second coupling agent, and a dispersant, with a mass ratio of 100:3~5:0.3~0.
8. The particle size D90 of the modified functional filler is <4μm.
2. The DAF film based on ultrasonic spraying according to claim 1, characterized in that, It should include at least one of the following technical features: (1) The thermally conductive filler is at least one of hexagonal boron nitride, aluminum nitride, silicon carbide, and silicon nitride; (2) The second coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane; (3) The dispersant is at least one of sodium polycarboxylate, ammonium polycarboxylate, sodium salt of polymethyl methacrylate-ethyl acrylate copolymer, and sodium salt of maleic acid-acrylic acid copolymer.
3. The DAF film based on ultrasonic spraying according to claim 1, characterized in that, It should include at least one of the following technical features: (1) The epoxy resin is at least one of bisphenol A type epoxy resin E-51, bisphenol A type epoxy resin E-44, bisphenol F type epoxy resin NPEF-170, and alicyclic epoxy resin ERL-4221; (2) The polyimide resin is at least one of the following: homopolymer polyimide resin, bisphenol A polyimide resin, and polyetherimide resin; (3) The latent curing agent is at least one of 2-ethyl-4-methylimidazolium, 1-benzyl-2-methylimidazolium, 2-phenyl-4,5-dihydroxyimidazolium, and methyltetrahydrophthalic anhydride; (4) The first coupling agent is at least one of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and vinyltriethoxysilane; (5) The epoxy resin and polyimide resin together comprise 100 parts; (6) The DAF membrane based on ultrasonic spraying also includes the following components by weight: 0.1 to 0.2 parts of defoamer, 0.2 to 0.4 parts of leveling agent, and 0.3 to 0.6 parts of toughening agent.
4. The method for preparing a DAF film based on ultrasonic spraying as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Step 1: Prepare modified functional fillers; Step 2: Prepare the spray adhesive solution; Step 3: Fix and preheat the protective film; Step 4: Ultrasonic-electrostatic synergistic spraying; Step 5: Gradient temperature-controlled drying and high-temperature curing.
5. The method for preparing a DAF film based on ultrasonic spraying according to claim 4, characterized in that, It should include at least one of the following technical features: (1) The method for preparing the modified functional filler in step 1 includes: Step 1.1: Mix the thermally conductive filler with the second coupling agent in proportion, so that the second coupling agent is evenly coated on the surface of the thermally conductive filler; Step 1.2: Add dispersant according to the ratio, and mix using a combination of high-speed dispersion and ultrasonic vibration; (2) The method for preparing the spray adhesive in step 2 includes: Step 2.1: Mix epoxy resin and polyimide resin in proportion as the main resin, add the remaining components and solvent in proportion, mix thoroughly to ensure that all components are completely dissolved; Step 2.2: Vacuum degassing and filtration; Step 2.3: Allow to stand and mature to obtain the spray adhesive solution; (3) Step 3, fixing and preheating the protective film, includes: laying the protective film flat on the vacuum adsorption heating plate, turning on the vacuum adsorption device, and preheating the heating plate at the same time.
6. The method for preparing a DAF film based on ultrasonic spraying according to claim 5, characterized in that, It should include at least one of the following technical features: (1) The mixing process in step 1.1 is to stir at a constant temperature of 70~90℃ for 1.5~2.5h; (2) In step 1.1, a protective gas is introduced during the mixing process. The protective gas includes at least one of nitrogen, helium, neon, and argon. (3) The high-speed dispersion speed in step 1.2 is 2500~3500 rpm, and the dispersion time is 25~35 min; (4) The oscillation frequency of the ultrasonic oscillation in step 1.2 is 40~60kHz, and the oscillation time is 25~35min; (5) The solvent used for mixing in step 2.1 is at least one of butanone, cyclohexanone, and propylene glycol methyl ether acetate; (6) The mixing process in step 2.1 is to stir at room temperature for 30~60 minutes; (7) The vacuum degassing pressure in step 2.2 is -0.09~-0.095MPa; (8) The pore size of the filter membrane used in step 2.2 is 4~6μm; (9) The resting and ripening time in step 2.3 is 1.5~3h; (10) The solid content of the spray adhesive obtained in step 2.3 is 30~40wt%, and the viscosity is 500~1500mPa·s; (11) The pressure of vacuum adsorption in step 3 is 0.06~0.08MPa; (12) The preheating temperature of the heating plate in step 3 is 50~60℃.
7. The method for preparing a DAF film based on ultrasonic spraying according to claim 4, characterized in that, It should include at least one of the following technical features: (1) Step 4 Ultrasonic-electrostatic synergistic spraying method includes: using ultrasonic spraying equipment and applying an external electric field to apply electrostatics, sending the spraying adhesive into the ultrasonic atomizer, and spraying the tiny droplets of the spraying adhesive. (2) Step 4, ultrasonic-electrostatic synergistic spraying process, adopts multi-layer thin spraying-cross spraying method.
8. The method for preparing a DAF film based on ultrasonic spraying according to claim 7, characterized in that, It should include at least one of the following technical features: (1) The ultrasonic atomization frequency in step 4 is 80~120kHz; (2) The diameter D of the microdroplets mentioned in step 4 is 5~10μm; (3) The voltage applied in step 4 is 8~25kV; (4) In step 4, the spraying air pressure is 0.1Mpa~0.2Mpa, the spraying distance is 15~25cm, and the spraying speed is 5-12m / min; (5) During the ultrasonic-electrostatic synergistic spraying process in step 4, the spray gun is always perpendicular to the protective film surface; (6) In step 4, the thickness of a single layer of wet film sprayed by multi-layer thin spraying is 8~15μm, and the total thickness of the wet film sprayed is 40~180μm. (7) In step 4, the cross-spraying angle between adjacent layers is 45°~90°; (8) In step 4, the overlap rate of the trajectory of two adjacent sprays during the single-layer spraying process is 30%~50%.
9. The method for preparing a DAF film based on ultrasonic spraying according to claim 4, characterized in that, Step 5, the gradient temperature control drying and high temperature curing method, includes: sending the sprayed wet film together with the vacuum adsorption heating plate into a multi-zone gradient oven, and sequentially staying in each temperature zone with increasing temperature gradient to obtain a DAF film. Preferably, the multi-zone gradient oven includes four temperature zones, and the temperature gradients of the four temperature zones are 65~75℃, 90~100℃, 110~120℃, and 125~135℃ respectively. More preferably, the dwell time in each temperature zone is 1-2 minutes, and the total dwell time in the four temperature zones is 5-8 minutes.
10. The application of the DAF film based on ultrasonic spraying as described in any one of claims 1 to 3, and the DAF film prepared by the preparation method as described in any one of claims 4 to 9, in 8-12 inch wafer and chip packaging.
Citation Information
Patent Citations
Spray coatable adhesive for bonding silicon dies to rigid substrates
US20110319513A1
Package process, DAF replacement
US20220028819A1
